Occurrence and Distribution of Nonfalciparum Malaria Parasite Species Among Adolescents and Adults in Malawi. (9th July 2021) - Gumbo, Austin; Topazian, Hillary M; Mwanza, Alexis; Mitchell, Cedar L; Puerto-Meredith, Sydney; Njiko, Ruth; Kayange, Michael; Mwalilino, David; Mvula, Bernard; Tegha, Gerald; Mvalo, Tisungane; Hoffman, Irving; et al.
Abstract: Background: Plasmodium falciparum malaria dominates throughout sub-Saharan Africa, but the prevalence of Plasmodium malariae, Plasmodium ovale spp., and Plasmodium vivax increasingly contribute to infection in countries that control malaria using P. falciparum -specific diagnostic and treatment strategies. Methods: We performed quantitative polymerase chain reaction (qPCR) on 2987 dried blood spots from the 2015–2016 Malawi Demographic and Health Survey to identify presence and distribution of nonfalciparum infection. Bivariate models were used to determine species-specific associations with demographic and environmental risk factors. Results: Nonfalciparum infections had broad spatial distributions. Weighted prevalence was 0.025 (SE, 0.004) for P. malariae, 0.097 (SE, 0.008) for P. ovale spp., and 0.001 (SE, 0.0005) for P. vivax . Most infections (85.6%) had low-density parasitemias ≤ 10 parasites/µL, and 66.7% of P. malariae, 34.6% of P. ovale spp., and 40.0% of P. vivax infections were coinfected with P. falciparum . Risk factors for P. malariae were like those known for P. falciparum ; however, there were few risk factors recognized for P. ovale spp. and P. vivax, perhaps due to the potential for relapsing episodes. Conclusions: The prevalence of any nonfalciparum infection was 11.7%, with infections distributed across Malawi. Continued monitoring of Plasmodium spp. becomes critical as nonfalciparum infections become important sources of ongoing transmission. Abstract : Using dried blood spots from the 2015–2016 Malawi Demographic and Health Survey, we assess spatial distribution of P. malariae, P. ovale spp., and P. vivax infection nationally, and compare differences in prevalence due to demographic and environmental risk factors.